Correction to: The genomic and clinical landscape of fetal akinesia (Genetics in Medicine, (2020), 22, 3, (511-523), 10.1038/s41436-019-0680-1) - Pergande, Matthias; Motameny, Susanne; Özdemir, Özkan; Kreutzer, Mona; Wang, Haicui; Daimagüler, Hülya Sevcan; Becker, Kerstin (Springer Nature, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper. © 2020, American College of Medical Genetics and Genomics.
Keywords: erratum